WAKTU GENERASI BAKTERI Escherichia coli BERDASARKAN VARIASI PH MEDIA EOSIN METHYLENE BLUE AGAR MEDIA - Diah Lestari; Indah Prasetyowati; Mega Mirawati (Fakultas Kedokteran UPN Veteran Jakarta Kerja Sama KNPT, 2023)
Bacteria require optimum environmental conditions to support cell growth and reproduction. States that are less than optimal cause bacteria to adapt and can infect humans for invasion of other organs. The speed of bacteria to infect is influenced by the rate and time of generation of bacteria in multiplying cells. This study aims to determine the effect of variations in pH (4,8; 5,8; 6,8; 7,8; and 8,8) in Eosin Methylene Blue Agar (EMBA) media on the generation time of Escherichia coli bacteria. Researchers used the True Experiment Post Only Control Design and One Way ANOVA test. The results showed that at a variation of pH 4,8 there was no growth; pH 5,8 with a generation time of 1,5-24,9; pH 6,8 with a generation time of 1,5-21,7 minutes; pH 7,8 with a generation time of 1,6-22,3 minutes; and pH 8,8 with a generation time of 1,6-22,8 minutes. The study concludes is that there is a significant effect of the variation in pH of the EMBA media on the generation time of Escherichia coli bacteria with a p-value of 0,000 < α 0,05, with the fastest generation time at pH 6,8.